(3QSGdI aj CMcGe GdejQGKs - (3GdOQGRj GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3GdeTJi dg HPdc hdG jbhe ebGeg ef GdOdGdI de jSJMb CLQg (B... (3GdCLQI eY CeQg Ch eG aj Mceg hdh CLGR GdHjY hGdTQGA hZjQgeG dCfg HGdaYd de JSJMb decGf GdJHQY (B...s
(3BNQgG (B:s
...(3aEPG bQfJ HGdEScGf bjd Scfi dcGf jbhd CScfJc gPg GdOGQ hdc ScfGg hHGdYeQ bjd YeQj cbhdc CYeQJc gPg GdCQV YeQc Ch YeQj (B... (3bjd QbHJj cCf jbhd CQbHJc gPG GdeJGM eOI cPG ef GdGbJQGH (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\215s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis